CUSTOMER EXPERIENCE AND ITS INFLUENCE ON CUSTOMER LOYALTY MEDIATED BY CUSTOMER SATISFACTION (Case Study on Consumers of PT. TELKOM MANADO) - Merry Ratar; Jourie Pangemanan; Tirsa Mamangkai; Sammy Rommy Novie Korua; Evans E.W. Tulungen (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This study aims to determine how much Customer Experience influences Customer Satisfaction. How much Customer Experience influences Customer Loyalty. How much Customer Satisfaction influences Customer Loyalty. How much Customer Experience influences Customer Loyalty mediated by Customer Experience at PT. Telkom Manado. The research approach used in this study is quantitative research with quantitative deductive logic/reasoning. Descriptive statistical analysis in this study is used to provide information about the identity of the respondents. The second is multivariate statistical analysis, namely the data analysis technique used in this study using SEM-PLS (Structural Equation Modeling-Partial Least Square). With SmartPLS (Partial Least Square) software. The results of the study show that Customer Experience has a positive effect of 0.647 on customer loyalty. Customer Experience has a positive effect of 0.785 on customer satisfaction. Customer Satisfaction has a positive effect of 0.311 on customer loyalty. Customer Experience has a positive and significant effect or 0.000 <0.05 on customer loyalty. Customer Experience has a positive and significant effect or 0.000 <0.05 on customer satisfaction. Customer Satisfaction does not have a positive and significant effect or 0.446 > 0.05 on customer loyalty. Customer satisfaction is not able to mediate the customer experience variable on customer loyalty, for the original sample shows a positive value direction of 0.244 while the significance level is 0.534 > 0.05.